Lexical Richness of the Expository Writing in Indonesian Senior High School Students - ASTRIDYA, FARA WAHYU (Lingual Journal of Language and Culture, 2018)
Learning a foreign language is often related to knowing the words which called lexical richness. This current study investigate the lexical richness in senior high school students. The data are taken from the students’ writing on expository essay. Writing an expository essay is a challenge for students where they should be able to write based on a given theme using a varied vocabulary so later the students are capable making a good writing. The students are collected from three grades that consist of 30 students in each grades. By the total amount of the students, it will be measured by some types of lexical richness; lexical density, lexical sophistication, and lexical variation. After being investigated, the results were found that lexical richness in each grades showed a significant increase in each class, starting from grade 10 to grade 12. According to all those three measurements, showed that grade 12 is the highest percentages among others and it concludes that students in grade 12 is the most prepared and have the richest lexical between grade 10 and 11.